Unraveling the Mystery Surrounding Post-Acute Sequelae of COVID-19 - Ramakrishnan, Rakhee K.; Kashour, Tarek; Hamid, Qutayba; Halwani, Rabih; Tleyjeh, Imad M. (Frontiers in Immunology, 2021)
More than one year since its emergence, corona virus disease 2019 (COVID-19) is still looming large with a paucity of treatment options. To add to this burden, a sizeable subset of patients who have recovered from acute COVID-19 infection have reported lingering symptoms, leading to significant disability and impairment of their daily life activities. These patients are considered to suffer from what has been termed as “chronic” or “long” COVID-19 or a form of post-acute sequelae of COVID-19, and patients experiencing this syndrome have been termed COVID-19 long-haulers. Despite recovery from infection, the persistence of atypical chronic symptoms, including extreme fatigue, shortness of breath, joint pains, brain fogs, anxiety and depression, that could last for months implies an underlying disease pathology that persist beyond the acute presentation of the disease. As opposed to the direct effects of the virus itself, the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is believed to be largely responsible for the appearance of these lasting symptoms, possibly through facilitating an ongoing inflammatory process. In this review, we hypothesize potential immunological mechanisms underlying these persistent and prolonged effects and describe the multi-organ long-term manifestations of COVID-19.